Implementation HR information system – part of a unified information environment of MPEI - I. M. Krepkov; M. R. Ovsyannikova; S. A. Petrov; A. B. Fedorov (Открытое образование (Москва), 2016)
The article is devoted to the unified information environment of National Research University “Moscow Power Engineering Institute” (MPEI), and its most important component – the HR information system. The article describes the architecture of the unified information space of MPEI. The main objective of the development of the HR information system – to provide access to users, including other information systems, to actual information about employees of MPEI.HR information system are based on many years of operating experience of the previous system and the like, are available on the market today, taking into account the decisions of personnel. The earlier HR information system was developed in 1995–1997 and used until mid-2015. In the process of its using it has accumulated a large number of «patches» and requests for revision that was stopped by limitations in the platform and solutions architecture. Comparative analysis of 1C and SAP products showed that the cost of implementation, configuration and maintenance of these products is higher than developing new solutions. Package of Microsoft technology software was chosen as a platform. These technologies have proven themselves in the development of similar projects, and vendor solutions for a long time support all key processes of information systems. Important is the presence of the selected software Microsoft FSTEC certificates (Federal Service for Technical and Export Control), which support the use of these products for storing and processing information in accordance with the laws of the Russian Federation. The MPEI has already implemented a number of systems on the Microsoft platform – postgraduate register, an Internet portal, etc. The use of technology of one supplier facilitates the integration processes and products into a unified information environment. The article details the technical and hardware specifications of the HR information system. The result of the work on the HR information system is stably functioning, supporting all business processes of the subject area and have successfully integrated within other software system. In addition to the «standard» option for storing information about employees («core» fields of the form, documents, various types of information on professional development, incentives, penalties, planned and actual vacations, etc..). HR information system has its own mechanism for the generation of orders and changes as a result of their approval. The subsystem orders included several modules: route editor, layout editor, orders editor, rights editor. Route Editor allows you to describe the route of the order to determine the movement and «point» statement, which if it enters the data into HR information system have to be updated on the basis of the text of the order. Template Editor is used to describe the future of the text of the order, the parameters that must be requested from the members of their processing before entering the text and action in approving an order. The orders editor works on the basis of a template, and provides opportunities for the formation of the order of the text and its harmonization in the course of the route and approval. The rights editor is used to distinguish the rights when dealing with orders subsystem. This article contains more detailed information about the frames of program of HR information system.In conclusion contained the positive experience of exploitation of the system and the introduction of a general trend to develop and support another IT solutions.